Polimorfismos de genes associados à resposta imune humoral em indivíduos naturalmente infectados pelo Plasmodium vivax no Estado do Pará - Cassiano, Gustavo Capatti [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Malaria is one of the main causes of morbidity and mortality in the tropics and subtropics areas of the world. Although the immunity is only partial, it is important in reducing the amount of illness and death caused by malaria. However, the immunity against malaria is complex, and one of the main goals of vaccine developers is to understand why people differ in their immune response to the parasite. The present research aims to investigate the genetic mechanisms related to humoral immune response against P. vivax blood stages antigens, predominant malaria species in Brazil. Nine single nucleotide polymorphisms (SNPs) in 7 genes (CD28, CTLA4, ICOS, CD86, CD40, CD40L e BLYS) were determined by PCR-RFLP. A total of unrelated 227 individuals infected with P. vivax from the Goianésia do Pará, Pará state, participated in this study. Level and prevalence of IgG antibodies against N-terminal (ICB2-5) and C-terminal (MSP-119) regions of MSP-1, DBP and AMA-1 of P. vivax were measured by ELISA. First, we evaluate the influence of genomic ancestry on distributions of co-stimulatory genes polymorphisms in an admixed Brazilian population using ancestry informative markers. ICOS, CD40L and CD86 polymorphisms were associated with genomic ancestry. There were significant association between CD28 -372G>A, ICOS +1564T>C, and CD40L -726T>C SNPs with antibodies anti-DBP prevalence. Moreover, CD40 -1C>T and CD86 +1057G>A SNPs were associated with antibody levels anti-PvMSP-119. The CD28 -372G>A and CD40 -1C>T SNPs were associated with IgM prevalence against ICB2-5. Haplotypes formed by polymorphisms in CD28, CTLA4, and ICOS genes were associated with IgG4 antibodies against ICB2-5. This is the first study to associate polymorphisms in costimulatory genes with humoral immune response against P. vivax. These data may add important information for understanding the immunological aspects involved in vivax malaria

A malária é uma das principais causas de morbidade e mortalidade nas áreas tropicais e subtropicais do mundo. O desenvolvimento de uma resposta imune eficaz é capaz de reduzir a mortalidade e os sintomas clínicos da doença. No entanto, este é um processo complexo, e um dos objetivos dos imunologistas é entender as razões pelas quais os indivíduos diferem em suas respostas imunes contra o parasito. O objetivo do presente estudo foi avaliar a influência de polimorfismos em genes coestimulatórios do sistema imune na resposta imune humoral contra proteínas de estágio sanguíneo do Plasmodium vivax, principal espécie causadora de malária no Brasil. Para tanto, nós genotipamos, pelo método de PCR-RFLP, nove SNPs em sete genes (CD28, CTLA4, ICOS, CD86, CD40, CD40L e BLYS). A amostra foi constituída por 227 indivíduos infectados com P. vivax no município de Goianésia do Pará, no Estado do Pará. As respostas de anticorpos IgG específicos contra as proteínas N- (ICB2-5) e C-terminal (MSP-119) da MSP-1, da DBP e da AMA-1 do P. vivax foram determinadas por ELISA. IgM e as subclasses de IgG contra a ICB2-5 também foram avaliadas. Para estudar os polimorfismos dos genes coestimulatórios, nós primeiramente investigamos o impacto da estratificação da população na distribuição dos polimorfismos com o auxilio de marcadores informativos de ancestralidade e demonstramos que a frequência dos SNPs ICOS +1564T>C, CD40L -726T>C e CD86 +1057G>A varia de acordo com a ancestralidade. Polimorfismos em genes coestimulatórios foram associados com a resposta de anticorpos contra proteínas do estágio sanguíneo do P. vivax, mais especificamente contra a DBP, e as porções N- e C-terminal da MSP-1. Além disso, haplótipos formados pelos genes CD28, CTLA4 e ICOS foram associados com a resposta de anticorpos IgG4 contra a região N-terminal da MSP-1. Este é o primeiro estudo de associação genética envolvendo polimorfismos em genes ...
Keywords: Genetica humana; Malaria - Aspectos genéticos - Pará; Polimorfismo (Genetica); Plasmodium vivax - Pará; Imunogenetica; Human genetics